LAHAN BASAH BUATAN UNTUK PENGOLAHAN AIR LIMBAH GREY WATER MENGGUNAKAN SALVINIA ROTUNDIFOLIA - Salsabila, Difa; Aphirta, Sarah; Hendrawan, Diana; Marendra, Sheilla (Universitas Trisakti, 2024)
Household wastewater consists of 80% grey water and 20% black water. The decline in water quality can have adverse impacts on well-being. Constructed wetland is an engineered system designed to harness the ecological principles of natural wetlands to address water pollution issues. The Free Water Surface system within the constructed wetland involves the flow of water on the surface. An appropriate plant example for use in a constructed wetland is Salvinia rotundifolia. Plant acclimatization was carried out for 12 days. The reactor operation continued for 12 days using a continuous system. The percentage removal of parameters in the constructed wetland reactor were as follows: COD 23.40-84.38%, BOD 37.93-72.73%, TSS 43.24-85%, phosphate 59.47-65%, and nitrate 10.99-31.08%. The values of areal removal rate constant (kA) and volumetric removal rate constant (kV) for the constructed wetland reactor were as follows: for COD, 1.48-3.75 m/day and 0.80-22.28 /day; for BOD, 1.70-3.73 m/day and 1.43-15.59 /day; for TSS, 2.11-8.83 m/day and 1.70-22.77 /day; for phosphate, 1.40-6.61 m/day and 2.89-11.20 /day; and for nitrate, 0.18-2.32 m/day and 0.58-1.54 /day. This study demonstrates that the constructed wetland reactor with Salvinia rotundifolia plants achieves removal efficiencies of up to 85%, thus meeting the standards set by the Minister of Environment and Forestry Regulation No. 68 of 2016 regarding Domestic Wastewater Quality Standards.